The Role of Doctor's Advice in the Process of Breastfeeding - Axmadjonova Zuxraxon Akmaljon qizi; Xolmatova Nurxon Olimovna (Zien Journals, 2022)
This article aims to explain the importance of breast milk in the nutrition of mothers after childbirth. The article mainly selected mothers who gave birth to their first child. The benefits of breastfeeding were explained to them. The need to protect and support breastfeeding It has been shown that the advice of health professionals working with mothers is helpful.
Keywords: breast milk; care; mastitis; artificial feeding